Spatio-temporal patterns of PAHs, PCBs and HCB in sediments of the western Barents Sea - Zaborska, Agata; Carroll, Jolynn; Pazdro, Ksenia; Pempkowiak, Janusz (Oceanologia, 2011)
Source at https://doi.org/10.5697/oc.53-4.1005 . We examine the composition and levels of organic contaminants (PAHs, PCB, HCB) in four sediment cores collected from the Barents Sea. We assess the influence of temporal variations in contaminant supplies and post-depositional reworking on contaminant distribution. Anthropogenic levels of ∑ 12PAH reached 95 ng g −1 , higher inventories dominated by BKF were observed at southern stations, while northern stations exhibited lower inventories with PHE as the dominant compound. The PCB composition was similar at all stations dominated by CB 101, 138 and 153. ∑7PCB concentrations were higher at northern stations. The observed composition and spatio-temporal pattern of organic contaminants is in accordance with long-range transport supplies.